Relationship Between Online Gaming Addiction with The Quality of Sleep Teenage in SMAN 1 Cimaragas Class XII - Hani Handayani; Dicky Firmansyah; Indra Gunawan; Sri Mulyanti; Asep Setiawan; Heri Budiawan (HealthCare Nursing Journal, 2024)
Online games are electronic and visual based games with the Internet as the medium. Online games are very popular nowadays with a wide range of players, one of whom is schoolchildren. The popularity of online games has a huge impact on young people as it can cause addiction and will release time to sleep to play online games that will affect the quality of sleep. This study aims to find out the relationship between online gaming addiction and with The Quality of Sleep Teenage in SMAN 1 Cimaragas class XII. The design of this study is Cross Sectional. The population of all the students playing online games in SMAN 1 Cimaragas class XII is 56 people. Sampling technique using total sampling with total samples is 56. The research instrument used questionnaires and data analysis using the Chi-Square correlation test. The results of the study obtained mostly highly addicted to online gaming as many as 47 people (83.9%) and the quality of sleep mostly had poor sleep quality as much as 50 people (89.3%). The conclusion is that there is a significant relationship between online gaming addiction and teenage sleep quality in SMAN 1 Cimaragas Class XII. For SMAN 1 schools, Cimaragas should give all students information about the dangers of online gambling addiction.